ANALISIS MATERI PEMBELAJARAN BAHASA ARAB PADA BUKU “ BAHASA ARAB BAKU DAN MODERN AL-LUGHAH AL-‘ARABIYYAH AL-MU’ASHIRAH ” Karya Prof. Dr. Eckehard Schulz - Anisa Ruyani Nisa (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2023)
Abstract Textbooks are a very important component in helping the Arabic language learning curriculum in the classroom. The book Al-Lughoh Al-Arabiyah Al-Mu'asyiroh is one of the books used; as a teaching tool, this book truly meets textbook standards because it fulfills the four main requirements of a textbook, namely selection, gradation, presentation, and repetition and is based on the calculated research results with a total score of 87.5% in the